2007
DOI: 10.1590/s0037-86822007000500021
|View full text |Cite
|
Sign up to set email alerts
|

Reposição de cães em área endêmica para leishmaniose visceral

Abstract: Esse trabalho objetivou estimar a reposição de cães em área endêmica para leishmaniose visceral, onde a eutanásia de animais soropositivos é indicada como medida de controle, e avaliar os motivos que levaram a aquisição ou não de novos animais. Houve a reposição em 44,5% dos casos, principalmente devido à necessidade de companhia ou guarda. O principal motivo para a não-reposição foi o temor da leishmaniose visceral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
0
10
0
3
Order By: Relevance
“…Nunes et al (2008) in a study conducted in an endemic area for CVL in Brazil found that about 40% of dogs were replaced with an average time of four months, and at nine months of follow-up of the replacement dogs, 42% of them were already serum reagents for CVL. The euthanasia of dogs with CVL seems to influence the structure of the canine population rather than its size, leading to the increase in the young portion of the canine population that may also have severe epidemiological consequences on other diseases, such as rabies, because these animals may not be vaccinated (Andrade et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nunes et al (2008) in a study conducted in an endemic area for CVL in Brazil found that about 40% of dogs were replaced with an average time of four months, and at nine months of follow-up of the replacement dogs, 42% of them were already serum reagents for CVL. The euthanasia of dogs with CVL seems to influence the structure of the canine population rather than its size, leading to the increase in the young portion of the canine population that may also have severe epidemiological consequences on other diseases, such as rabies, because these animals may not be vaccinated (Andrade et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Educational actions directed to the population should accompany euthanasia of serum dogs reacting to CVL. In endemic areas, responsible tenure programs may be more useful for VL control than canine population control means (Andrade et al 2007). In the municipality of Iguatama, no educational actions were carried out at any time, which may have impaired the effectiveness of euthanasia as a method of controlling CVL.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of all those limitations a relevant number of reports could be reviewed in detail, showing no strong evidence for a significant impact on VL transmission for any of the interventions reviewed. Canine culling seems to be the least acceptable intervention at community level for obvious reasons and has low efficiency due to high replacement rate of eliminated dogs with susceptible puppies [103],[115],[116]. Vector control interventions are better accepted by the affected populations and mathematical models suggested encouraging efficacy, but they need further study.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that only the removal of seropositive dogs and spraying of buildings does not control the occurrence of infection in dogs by Leishmania sp. One example of this was described in the municipality of Araçatuba where 45% houses with a dog euthanized due to leishmaniases replaced the dog in a period of one year [23]. …”
Section: Final Considerationsmentioning
confidence: 99%